2018
DOI: 10.18520/cs/v115/i11/2052-2062
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Sources of Soil Organic Amendments for Sustaining Soil Health and Crop Productivity in India – Impacts, Potential Availability, Constraints and Future Strategies

Abstract: Among the several causes, critical low soil organic matter status is predominant for decline in soil health and consequent fall in crop productivity. Over the years, availability of traditional source of soil organic amendment, viz. cattle manure drastically declined due to various reasons (domestic uses as fuel and plastering of the kachha houses). The present study highlights that there are many alternative sources of soil organic amendments available in the country which have tremendous potential to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…It is also clear that the yield response to the application of increasingly more expensive chemical inputs is falling. Indoria et al (2018) show that the average crop response to fertilizer use has fallen from around 25 kg grain/kg of nitrogen, phosphorus, and potassium (NPK) fertilizer during the 1960s to a mere 6 kg grain/kg NPK by 2010 (Figure 1). This has meant higher costs of cultivation without a corresponding rise in output, even as this intensified application of inputs compels farmers to draw more and more water from below the ground.…”
Section: Crisis Of the Green Revolutionmentioning
confidence: 99%
“…It is also clear that the yield response to the application of increasingly more expensive chemical inputs is falling. Indoria et al (2018) show that the average crop response to fertilizer use has fallen from around 25 kg grain/kg of nitrogen, phosphorus, and potassium (NPK) fertilizer during the 1960s to a mere 6 kg grain/kg NPK by 2010 (Figure 1). This has meant higher costs of cultivation without a corresponding rise in output, even as this intensified application of inputs compels farmers to draw more and more water from below the ground.…”
Section: Crisis Of the Green Revolutionmentioning
confidence: 99%
“…(Jepson et al, 2020) It is also clear that the yield response to the application of increasingly more expensive chemical inputs is falling. Indoria et al (2018) show that the average crop response to fertiliser use has fallen from around 25 kg grain/kg of nitrogen, phosphorus and potassium (NPK) fertiliser during the 1960s to a mere 6 kg grain/kg NPK by 2010 (Fig. 3).…”
Section: Wheels Come Off the Green Revolutionmentioning
confidence: 99%
“…Further, it has been reported that the addition of organic matter through farmyard manure and crop residues played a crucial role to determine the soil physical (Indoria et al 2016) and chemical and biological functional capacity of soil (Sharma et al 2017;Indoria et al 2018). It has also been well proved that the soil organic carbon significantly improved the physical soil quality parameters by supplying the organic matter, carbon and energy to various microbes, which secrete various enzymes and enhance soil aggregation and in-turn resulted in positive effect on various soil physical properties.…”
Section: Some Research Experiences On the Effect Of Conservation Agriculture And Other Resource Conservation Practices On Soil Quality Immentioning
confidence: 99%